Posted by **Anonymous** on Sunday, March 31, 2013 at 9:59am.

5) Consider the equations:

f(X)= -6x-1 and g(x)=4x^2

Select the solution for (f+g)(x).

a) -6x -1 + 4x^2

b) -24x^3 - 4x^2

c) -24x^2 - 1

d) -6x - 1- 24x^2

## Answer This Question

## Related Questions

- Math - consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (...
- algebra - Did I do this problem the correct way if so is there a shorter way to ...
- alg2 check? - solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x...
- Maths - is this correct... (3x^2+4x-3)^2-(3x^2-x+2)^2 then is it this (9x^4+24x^...
- MATH - f(x)= -6x-1 and g(x)=4x^2 select the soultion for (f+g)(x) stuck not sure...
- math help please - 12. (-8x) x (3x^2) -5x^3 -24x^2 -24x^3 -5x^2 13. (-11z)^0 z 1...
- MATH - F(X)=-6-1 AND G(X)=4X^2 WHAT WOULD THE SOLUTION FOR (FG) (X) BE. im stuck...
- Math - (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+...
- math - Use polynomial long division to divide -4x^3 + 24x^2 – 24x + 4 by x^2 – ...
- math - which pair of expressions are equivalent A 4(6X) and 10X B 4(6X) and 24X ...

More Related Questions